Peripheral Bone Densitometry Measurement with Radiographic Absorbtiometry (RA) versus Spine and Femur Dual X-Ray Absorbtiometry (DXA) Measurements - Balci, T. A.; Koc, Z. P. (Springer, 2011)
[Abstract Not Available]